Protocol for Pertussis Immunisation and Food Allergy (PIFA): A case-control study of the association between pertussis vaccination in infancy and the risk of IgE-mediated food allergy among Australian children - Estcourt, M.; Marsh, J.; Campbell, D.; Gold, M.; Allen, K.; Richmond, P.; Waddington, C.; Snelling, Thomas (BM J Group, 2018)
© Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted. Introduction Atopic diseases, including food allergy, have become a predominant cause of chronic illness among children in developed countries. In Australia, a rise in hospitalisations among infants coded as anaphylaxis to foods coincided with the replacement of whole-cell pertussis (wP) vaccine with subunit acellular pertussis (aP) vaccine on the national immunisation schedule in the late 1990s. Atopy is characterised by a tendency to mount T helper type 2 (Th2) responses to otherwise innocuous environmental antigens. Compared with infants who receive aP as their first pertussis vaccine, those who receive wP appear less likely to mount Th2 immune responses to either vaccine or extraneous antigens. We therefore speculate that removal of wP from the vaccine schedule contributed to the observed rise in IgE-mediated food allergy among Australian infants. Methods and analysis This is a retrospective individually matched case-control study among a cohort of Australian children born from 1997 to 1999, the period of transition from wP to aP vaccines; we include in the cohort children listed on Australia's comprehensive population-based immunisation register as having received a first dose of either pertussis vaccine by 16 weeks old. 500 cohort children diagnosed as having IgE-mediated food allergy at specialist allergy clinics will be included as cases. Controls matched to each case by date and jurisdiction of birth and regional socioeconomic index will be sampled from the immunisation register. Conditional logistic regression will be used to estimate OR (±95% CI) of receipt of wP (vs aP) as the first vaccine dose among cases compared with controls. Ethics and dissemination The study is approved by all relevant human research ethics committees: Western Australia Child and Adolescent Health Services (2015052EP), Women's and Children's Hospital (HREC/15/WCHN/162), Royal Children's Hospital (35230A) and Sydney Children's Hospital Network (HREC/15/SCHN/405). Outcomes will be disseminated through publication and scientific presentation. Trial registration number NCT02490007.